TRANSGENDERING CELEBRATIONS: THE POLITICS OF SEXUALITY IN KOOVAGAM AND KOTTANKULANGARA CHAMAYAVILAKKU. - SONYA J. NAIR
With gender speak gaining volume and lexical complexity over the ages, it becomes imperative that the factors that have come together to consolidate our perceptions of gender and sexuality be examined. The sociological, religious and colonial drives that have been documented also contain within them the coded narratives of the need for sexual conformity that are not far from our current concepts of eugenics. Religion, especially Christianity, when combined with the colonial agenda was a potent crusade-like force that left far reaching effects on cultures worldwide. Modernity and its implications are yet another concern of this paper. The interesting position that the transgender occupies in the midst of such deliberations is examined in the context of body, nationhood, life chances and the jostle for an economy backed identity. As a round up the paper takes into account the fomenting of a transgender lexicon that is trying to validate itself through invoking infallible allies (culture, religion)- which were once the favoured tools of the agents of an earlier modernity project.